Cardiovascular diseases in Paralympic athletes. Issue 17 (26th May 2016) - Pelliccia, Antonio; Quattrini, Filippo M; Squeo, Maria Rosaria; Caselli, Stefano; Culasso, Franco; Link, Mark S; Spataro, Antonio; Bernardi, Marco
Abstract : Background: Sport participation (SP) of individuals with impairments has recently grown exponentially. Scarce scientific data, however, exist regarding cardiovascular (CV) risk associated with competitive SP. Objective: Assessing the prevalence of CV abnormalities and the risk for SP in Paralympic athletes (PA). Methods: PA (n=267; 76% men), aged 35±9 years, engaged in 18 sport disciplines, with a spectrum of lesions including: spinal cord injury (paraplegia and spina bifida) (n=116); amputation, poliomyelitis, cerebral palsy and other neuromuscular and/or skeletal disorders (Les autres) or visual impairment (n=151) entered the study. CV evaluation included history, PE, 12-lead and exercise ECG, echocardiography. Of these, 105 participated in ≥2 consecutive games, and had evaluations available over a 6±4 year follow-up. Results: Structural CV abnormalities were identified in 33 athletes (12%), including arrhythmogenic cardiomyopathies in 3, aortic root dilation in 3, valvular diseases in 7 (mitral valve prolapse in 4, bicuspid aortic valve in 3) and systemic hypertension in 11 (4%). In addition, ventricular (polymorphic, couplets or non-sustained ventricular tachycardia) or supraventricular tachyarrhythmias (atrial flutter, paroxysmal atrial fibrillation or SVT) were identified in 9 others. Over a 6-year follow-up, 6 of the 105 athletes (6%) developed CV diseases, including dilated cardiomyopathy in 1 and systemic hypertension in 5. Conclusions: PA present an unexpected high prevalence of CV abnormalities (12%), including a non-trivial proportion of diseases at risk for sudden death (2%), such as arrhythmogenic cardiomyopathies and dilated aortic root. This observation suggests that tailored recommendations for preparticipation screening and safe SP in this special athletic population are timely and appropriate.